Sensorineural Hearing Loss: A Rare Manifestation of Scrub Typhus - Athulya Asokan; Athira V R; Sanal K Thomas; Ajeesh Koshy (Achievements and Challenges of Medicine and Medical Science Vol. 2, 2024)
Scrub typhus, caused by Orientia tsutsugamushi, is a re-emerging infectious disease prevalent in countries like China, India, Indonesia, Japan, Korea, the Philippines, Sri Lanka, Taiwan, and Thailand and is an often underestimated public health problem in the Asia Pacific area. The "tsutsugamushi triangle" refers to a geographical region in the Asia-Pacific area where scrub typhus is highly endemic. This triangle spans from northern Japan and far-eastern Russia in the north, to northern Australia in the south, and to Pakistan and Afghanistan in the west. As an underestimated disease, there is still a substantial lack of knowledge about scrub typhus, reflected by the limited epidemiological data and insufficient public health information in its endemic regions. Without appropriate treatment, scrub typhus can lead to severe multiorgan failure, with a case fatality rate of up to 70%. While fever and systemic complications are common in scrub typhus, neurological manifestations, such as sudden bilateral sensorineural hearing loss (SNHL), are rare but increasingly recognized. A case of 64-year-old female presented who experienced fever, myalgia, and bilateral sensorineural hearing loss (SNHL), eventually diagnosed as scrub typhus. The diagnostic process was challenging due to the wide clinical spectrum and nonspecific symptoms of the disease. Proposed mechanisms for hearing loss include direct invasion of the central nervous system or vasculitis involving the cochlear nerve. Increased awareness among healthcare providers is essential for prompt diagnosis and treatment. In endemic areas, empirical treatment with doxycycline is advised for suspected cases. This case highlights the need to consider scrub typhus in patients with acute febrile illness and ear-related symptoms, which can lead to early intervention and better patient outcomes.